The Advantage and Limitation of Agriculture Byproduct and Feeding Strategy Based on Agriculture Byproduct for Beef Cattle - ., Mariyono; Krishna, N H (Indonesian Animal Sciences Society, 2009)
Feed supply is getting limited since the use of land for forages has been replaced by building industries big plantation, agriculture. Sustainable integration between animal and food crop and plantation is efficient and gives advantage for both. Rice, cassava soybean, groundnut, palm oil, coconut, coffee, cocoa and sugar cane are food crop and plantation which their byproducts are generallyÂ used or modified/processed for ruminant production. This paper describes optimization on the use of these byproducts to decrease feed cost without ignoring the feed quality. These byproducts have special characteristic and limitation with fluctuated price. Their nutritive values vary and they can be grouped into fiber, fiber-energy, fiber-protein, protein or energy sources. Therefore, special strategy for each location and purpose of livestock industry is required to get an efficient and optimal feed composition. Â Key words: Feed, agriculture byproduct, beef cattle